Emerging carrier‐free nanosystems based on molecular self‐assembly of pure drugs for cancer therapy. Issue 5 (7th April 2020) - Zhang, Xuanbo; Li, Na; Zhang, Shenwu; Sun, Bingjun; Chen, Qin; He, Zhonggui; Luo, Cong; Sun, Jin
Abstract: The potential toxicity of nanocarrier excipients and complicated preparation technologies have impeded the clinical application of nanomedicine. Recently, pure drug‐assembled nanosystems (PDANS) have been widely investigated, due to the unique self‐assembly characteristics of pure drug molecules. PDANS provides a facile nanoplatform for developing carrier‐free nanomedicine. Herein, the recent trends in PDANS for cancer therapy are outlined. First, the emerging strategies to develop single pure drug‐based nanoassemblies are discussed. Second, co‐assembly of two or more pure drugs for efficient combination therapy is overviewed. Then, the functional self‐assembly of non‐cytotoxic agents in tumor sites is presented. Finally, the rational design and self‐assembly mechanisms of these unique nanoplatforms are highlighted.